Adecuación de un entorno universitario con la implementación de apoyo audiovisual (Universidad Antonio Nariño - Sede Villavicencio) (2020)
Currently at the Universidad Antonio Nariño – Sede Villavicencio the aim is to improve the wellness and study environment for the entire educational community. For this purpose, this project, whose main objective is to adapt a university environment with the use of audiovisual aids for the benefit of all those who visit the facilities. Through a visual inspection of the sites within the university campus, it is visualized that, between the pool and the university wellness office, a place is available that is not using which is abandoned. Several university students were interviewed and asked about the perception of the site, the adjustments that would be made and its new use. The results based on the interviews led to the adaptation of the area for study and rest. Therefore, it is concluded that, when making the general modification of the site, it will enjoy positive influence and will improve the appreciation of students, teachers and the staff visiting the Universidad Antonio Nariño – Sede Villavicencio